ANALISIS JASA JOKI GAME ONLINE MOBILE LEGENDS DALAM PERSPEKTIF HUKUM EKONOMI SYARIAH - Ashari, Irfan (Fakultas Syariah (Syari'ah Faculty ), 2025)
Mobile Legends is an online game from China which was released by Moonton. Mobile Legends is a very popular online game with more than five hundred million downloads and users spread across various countries. With technology and online games increasingly developing, it influences a multi-level lifestyle. Initially, playing online games was only to relieve stress and for entertainment for the players. Most players consider the situation in the game to be normal. Currently, with online games, game players can make money by joining an e-sports team to become a professional player, selling game diamonds (game currency), selling game accounts, and so on. as well as opening jockey services to increase ranking or levels in the Mobile Legends game. Many consumers use jockey services because of their lack of ability in the game. Using the services of a jockey must pay attention to the terms and conditions of Ijarah, in Islam it is permissible to join in muamalah if you fulfill the terms and conditions of Ijarah